The Effect of Village Fund Management and Community Participation on the Distribution of Village Fund Direct Cash Assistance (BLT-DD) : (Case Study on Villages in Lolayan District, Bolaang Mongondow Regency) - Della Novita Mamonto; Lukman Pakaya; Surya Handrisusanto Ahmad (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of village fund management and community participation on the distribution of village fund direct cash assistance in villages in Lolayan District, Bolaang Mongondow Regency. The method used is quantitative by collecting primary data through the distribution of questionnaires to village officials and communities with a sample of 165 respondents. Data analysis used multiple linear regression with the help of SPSS 26. The results of the study show that partially the management of village funds has a positive and significant effect on the distribution of direct cash assistance. Likewise, community participation has a positive and significant effect on the distribution of direct cash assistance. Simultaneously, both the variables of village fund management and community participation have a significant positive effect on the distribution of direct cash assistance to villages in Lolayan District, Bolaang Mongondow Regency. The R squere value obtained shows a strong relationship between independent variables and dependent variables in this study.